The Secretome of Brain Endothelial Cells Exposed to the Pyrrolizidine Alkaloid Monocrotaline Induces Astrocyte Reactivity and Is Neurotoxic - Letícia Oliveira Santos; Julita Maria Pereira Borges; Juliana Lago Leite; Mauricio Moraes Victor; Adriana Lopes da Silva; Cleonice Creusa dos Santos; Victor Diógenes Amaral da Silva; Ravena Pereira do Nascimento; Silvia Lima Costa (Toxins)
Monocrotaline (MCT) has well-characterized hepatotoxic and pneumotoxic effects attributed to its active pyrrole metabolites. Studies have previously shown that astrocytes and neurons are targets of MCT, and that toxicity is attributed to astrocyte P450 metabolism to reactive metabolites. However, little is known about MCT toxicity and metabolism by brain endothelial cells (BECs), cells that, together with astrocytes, are specialized in xenobiotic metabolism and neuroprotection. Therefore, in the present study, we evaluated the toxicity of MCT in BECs, and the effects on astrocyte reactivity and neuronal viability in vitro. MCT was purified from Crotalaria retusa seeds. BECs, obtained from the brain of adult Wistar rats, were treated with MCT (1–500 µM), and cell viability and morphology were analyzed after 24–72 h of treatment. Astrocyte/neuron co-cultures were prepared from the cortex of neonatal and embryonic Wistar rats, and the cultures were exposed to conditioned medium (secretome) derived from BECs previously treated with MCT (100–500 µM, SBECM100/500). MCT was not toxic to BECs at the concentrations used and induced a concentration-dependent increase in cell dehydrogenase after 72 h of treatment, suggesting resistance to damage and drug metabolism. However, exposure of astrocyte/neuron co-cultures to the SBECM for 24 h induced changes in the cell morphology, vacuolization, and overexpression of GFAP in astrocytes, characterizing astrogliosis, and neurotoxicity with a reduction in the length of neurites labeled for β-III-tubulin, effects that were MCT concentration-dependent. These results support the hypothesis that MCT neurotoxicity may be due to products of its metabolism by components of the BBB such as BECs and astrocytes, which may be responsible for the brain lesions and symptoms observed after intoxication.